Penggunaan Sistem Informasi Geografi Untuk Mencari Lokasi yang Tepat Sebagai Penyimpanan Energi Hydro Terpompa - Taufiq Ejaz Ahmad (Universitas Prof. Dr. Hazairin, S.H, 2020)
Energy is a basic human need. All facilities that support the operation of renewable energy need a strategic site that is adequate and meets all aspects required, including geographical aspects. The difference in geographical character needs is based on the different energy conversion capabilities of each energy generation unit, this requires the developer to decide a strategic location and can support the greatest energy conversion. To make it easier to figure the location based on certain geographical criteria and as decision support can optimize the use of Geographic Information Systems. A study has been carried out in South Australia to develop a set of Geographic Information System algorithms to find the right location for the construction of PHES. The aim of the reviewer is to learn how the Geographic Information System algorithm can be applied in the search mechanism automatically and how it is alternative. In order to get the implementation aspects of the method reviewed.